The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/0974-7796.148595
|View full text |Cite
|
Sign up to set email alerts
|

Prostate laser vaporization is safe and effective in elderly men

Abstract: Introduction:There are few data on the safety and efficacy of laser photoselective vaporization (LVP) in elderly men. We compared the safety and efficacy of LVP for the treatment of symptomatic benign prostatic hyperplasia (BPH) in men ≥75 years, who we defined as elderly, to those <75 years.Materials and Methods:Safety and efficacy outcomes in elderly men undergoing LVP for lower urinary tract symptoms secondary to BPH from 2005 to 2012 were compared with men <75 years. Differences between-groups in demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Majumdar et al investigated prospectively the efficacy and safety of laser photoselective vaporization (LVP) in groups aged ≥75 (n=49) and <75 years (n=153). 24 In contrast to Castellani et al, the ≥75 age group’s median LOS was significantly longer (1 day vs 0 days; P = 0.001). In the 1st month follow-up, there was a significant improvement in median IPSS in both age groups (23 to 10 years in the younger group and from 19 to 16 in the elderly group; P < 0.001 and P = 0.01, respectively), while the elderly group’s IPSS was significantly higher than the younger group’s (16 vs 10; P = 0.01).…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Majumdar et al investigated prospectively the efficacy and safety of laser photoselective vaporization (LVP) in groups aged ≥75 (n=49) and <75 years (n=153). 24 In contrast to Castellani et al, the ≥75 age group’s median LOS was significantly longer (1 day vs 0 days; P = 0.001). In the 1st month follow-up, there was a significant improvement in median IPSS in both age groups (23 to 10 years in the younger group and from 19 to 16 in the elderly group; P < 0.001 and P = 0.01, respectively), while the elderly group’s IPSS was significantly higher than the younger group’s (16 vs 10; P = 0.01).…”
Section: Resultsmentioning
confidence: 57%
“…The study of Majumdar et al reported that the most common perioperative complications in the ≥75 age group were dysuria (10.2%), urinary tract infection (10.2%), and haematuria (10.2%). 24 They detected no significant difference between age groups in perioperative complications.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations